Marginalized Society in the City of Surabaya: A Proposal for Effective Solution - Probowati, Yusti (ANIMA Indonesian Psychological Journal, 2007)
Advance development of a city as big as Surabaya has created a sophisticated physical development. Nevertheless, on the other side it has enlarged the marginalized society. Marginalized society is a group of people which is due to many factors, they cannot take roles properly in the society. The number of marginalized society in East Java has been up to 26.27 % of total population, and most of them live in Surabaya. The aim of this article is to provide a description of marginalized society (such as street children, sex workers, beggars, the homeless, the homeless with psychosomatic disorder, and criminals), treatment by the government, and a proposal for effective solution from the perspective of psychology. Perkembangan pesat kota sebesar Surabaya telah menciptakan perkembangan fisik yang canggih. Namun, di sisi lain hal tersebut telah meningkatkan jumlah masyarakat yang terpinggirkan. Masyarakat yang terpinggirkan adalah kelompok orang yang karena berbagai sebab, tak mampu berperan secara tepat dalam masyarakat luas. Jumlah masyarakat terpinggirkan di Jawa Timur telah meningkat hingga 26.27 % dari seluruh populasi, dan sebagian besar tinggal di Surabaya. Tujuan artikel ini adalah mengenali masyarakat terpinggirkan (seperti anak jalanan, pekerja seks komersial, pengemis, tuna wisma, tuna wisma dengan kelainan psikosomatik, dan kriminal), penanganan oleh pemerintah, dan menyampaikan solusi efektif dari sudut pandang psikologi.